2006
DOI: 10.1111/j.1365-2850.2006.01001.x
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic sexual dysfunction and the protective withholding of information: in whose best interest?

Abstract: In recent years a growing body of evidence has highlighted the impact of neuroleptics and antidepressants on sexual function. Research from a service user's perspective suggested that service users are dissatisfied with the information that they received on drugs, and would like more education, in particular, on the side effects of medication that impact on sexual function. This paper reports some of the findings of a grounded theory study that explored how psychiatric nurses responded to issues of sexuality i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 40 publications
2
25
0
Order By: Relevance
“…This hindered their attempts to prepare for adverse side effects and adopt strategies that would help them to move forward. Our findings support previous research, which found withholding information about adverse sexual effects had the potential to increase isolation and distress amongst patients and inadvertently damage the therapeutic relationship between clinician and patient (Bahrick & Harris, 2009;Higgins, Barker & Begley, 2006). Whilst the specific reasons for withholding information were not included in the aim of our study, recent literature has identified a number of personal, structural and organisational factors that impede or facilitate a proactive discussion of sexual problems (Dyer & das Nair, 2013;Quinn et al, 2011).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This hindered their attempts to prepare for adverse side effects and adopt strategies that would help them to move forward. Our findings support previous research, which found withholding information about adverse sexual effects had the potential to increase isolation and distress amongst patients and inadvertently damage the therapeutic relationship between clinician and patient (Bahrick & Harris, 2009;Higgins, Barker & Begley, 2006). Whilst the specific reasons for withholding information were not included in the aim of our study, recent literature has identified a number of personal, structural and organisational factors that impede or facilitate a proactive discussion of sexual problems (Dyer & das Nair, 2013;Quinn et al, 2011).…”
Section: Discussionsupporting
confidence: 74%
“…There are similarities between this study and other studies that reported how mental health clinicians, in particular, perceive iatrogenic sexual difficulties as a male problem (Phillips, 2009;Quinn et al, 2011). Indeed, our findings seem to be consistent with one particular study by Higgins et al (2006), which reported that mental health clinicians perceived women to be less concerned about iatrogenic sexual difficulties and more willing to tolerate the adverse sexual effects. Our findings suggest that the inadvertent reinforcement of traditional sexual scripts had a negative impact on women's coping experiences and acted as a barrier to the therapeutic relationship.…”
Section: Discussionsupporting
confidence: 56%
“…Sexual dysfunction can have significant impact on the person’s quality of life, quality of relationships, self esteem, and recovery and can lead to noncompliance with antidepressant treatment with a potential for relapse of symptoms 1. Despite this and the frequency of researchers reporting antidepressant-associated sexual dysfunction within the literature, it continues to be underreported or underemphasized on client information leaflets, package inserts,2 and verbal information given to clients by practitioners 3…”
Section: Introductionmentioning
confidence: 99%
“…The failure of the SSRI-research literature to fully engage in addressing the psychological costs of medicationinduced sexual dysfunction suggests that clinicians may sometimes fail to invite fully collaborative interactions in response to patients' concern about SSRI-emergent sexual dysfunctions. Instead, they may engage in something more akin to what Higgens et al [26] describe as a "compliance monologue"[p. 441] motivated by, among other things, the professional's own discomfort with initiating an in-depth conversation about sexual functioning, bolstered by an a priori allegiance to a pharmacological model of treatment.…”
Section: Underestimation Minimization and Gaps In Knowledge About Smentioning
confidence: 99%